Today in breast augmentation - Calderón, Juan Manuel (2016)
Breast augmentation is one of the most commonly performed procedures worldwide among aesthetic reconstructive surgeries. Among the indications for performing the procedure are primary and secondary alterations related to breasts shape and volume. During the initial assessment, emphasis should be placed in the anamnesis and physical examination, allowing to define target sizing and realistic expectations to prospectively determine the possible postoperative satisfaction rates. There are several methods used to select the appropriate implants that have become more accurate with time and with the use of technology. Although there are multiple materials developed, to this moment silicone implants continue to be the ones most used worldwide with low complication rates depending on each patient and on the technique used. It is considered as one of the aesthetic reconstructive surgeries with the highest degree of acceptance among the general population who undergo this type of procedures.